The door of preoccupation with Arabic grammar between illusion and misunderstanding - المساعيد, ندوة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Preoccupation is one of the difficult grammatical chapters in which the student and the learner transcend the grammatical ruling to delve into issues related to the theory of grammar, such as the factor and what is done. This study came to examine the nature of the phenomenon; To reveal illusion and misunderstanding in this section, and to provide a logical explanation for the different rulings and the multiplicity of its issues; Having presented the concept of this section and its provisions in grammatical thought and the position of grammarians in it, ancient and modern; The study proves that Preoccupation is a linguistic style, and the control in it between nominative and accusative is the speaker's choice